Implementation of Changes in Village Status from Regional Device to Sub-Distric Devices in District of Bungo Dani Bungo Regency-Jambi Province - Septian Arifin (Institut Pemerintahan Dalam Negeri (IPDN), 2019)
Amendment to the law on Regional Government namely law number 23 of 2014 causea significant change, village organizations become sub-district device. The problemthat arises is the working relationship between the village head and the sub-districthead, performance of the village organization after changing regulations, andperformance of sub-district organization in supervising village. Research wasconducted in Bungo Dani sub-district Bungo Regency, Jambi Province. Purpose of thisStudy is to know implementation of changes the village become a sub-district device.Research method is qualitative research, because qualitative research is able tocapture phenomena in detail and can provide an overview for researchers. Techniqueof data collection is done by conducting interviews, observation and documentation.Result of the study generally went well, but there are several problems and obstaclesthat is, poor communication between village heads and sub-district heads, the causedoes not understand the applicable regulations, late disbursement of funds for villagefrom sub-district, and regulation of present data on urban village officials in the subdistrict.Conclusions and suggestions are that the process of implementing governmentactivities in general runs well, with some obstacles and problems. Suggestions, localgovernment must be more active in providing education and knowledge to theapparatus in the sub-district and village to the applicable regulations.